Green Legitimacy Strategies: Symbolic Convergence in The Sustainability Reports of Sido Muncul and BioFarma - Graha Wira Krida; Morissan Morissan; Ridzki Rinanto Sigit (Riviera Publishing, 2026)
The increasing demands on sustainable business practices encourage companies to not only demonstrate good environmental performance, but also communicate them effectively to stakeholders. However, there is still a gap between sustainability implementation and the company's ability to build legitimacy through persuasive communication. This study aims to analyze the green legitimacy strategy and the construction of the rhetorical vision built in the sustainability report of pharmaceutical companies that receive PROPER Gold in Indonesia. The research used a qualitative approach with a narrative analysis method based on Symbolic Convergence Theory (SCT) and Aristotle's rhetoric which includes ethos, logos, and pathos. Data was obtained from the sustainability reports of PT Bio Farma and PT Sido Muncul in 2024 which were analyzed through the identification of fantasy themes, structural themes, dynamic themes, and persuasion strategies. The results of the study show that PT Bio Farma builds legitimacy through the dominance of logos that emphasizes technological transformation, energy efficiency, and compliance with global ESG and SDGs standards. In contrast, PT Sido Muncul develops legitimacy through a balanced combination of logos, ethos, and pathos rooted in local cultural values, social harmony, and community empowerment. The findings of the study revealed that the rhetorical vision built by the two companies differed according to the characteristics of the intended stakeholders. This research enriches the study of sustainability communication by integrating the context of PROPER and Symbolic Convergence Theory in the analysis of the green legitimacy of pharmaceutical companies in Indonesia.